Impact of elearning on motivation and critical thinking ability of multimedia major vocational school students - Fardani, Tyo Wildan Afrizal; Sumbawati, Meini Sondang; Buditjahjanto, I Gusti Putu Asto; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2022)
This article aims to determine the impact of e-learning and students' motivation on students' critical thinking skills. The quantitative approach is to process data and numbers obtained through statistical analysis. Sources of data used in this study are primary data or data obtained directly from respondents. This study aims to examine the effect of the independent variable, namely e-learning (X1), students' learning motivation (X2) on the dependent variable, namely students' critical thinking ability (Y). Researchers took a sample of 118 respondents. Collecting data by giving questionnaires to respondents to all students majoring in multimedia at SMK Ketintang Surabaya. Based on data from the results of research and tests that have been conducted, it can be concluded that: (1) There is a significant contribution between e-learning and students' critical thinking skills. (2) There is a significant contribution between student learning and students' critical thinking skills. (3) There is a significant contribution between e-learning and student learning motivation towards students' critical thinking skills in the SMK Multimedia Expertise Program with a contribution value of 61.3%.